The ripple effect of surface water on dryland ecosystems - Amanda L. Subalusky; Christopher L. Dutton; Robert A. McCleery (Trends in Ecology & Evolution, 2026)

Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Understanding Postpartum Mothers’ Perspectives of Chrononutrition Approaches: A Qualitative Study - Elizabeth N. Davis; Zena A. Patel; Christie Kirchoff; Courtney M. Peterson; Gareth R. Dutton; Erin Contratto; Camille R. Schneider-Worthington (Journal of the Academy of Nutrition and Dietetics, 2026)

ShellBank: traceability toolkit and global database of marine turtle DNA - Michael P. Jensen; Greta J. Frankham; Carla Alonso O’Friel; Erin L. LaCasella; Kelly I. Morgan; Maftuna Sola; Lucy M. I. Webster; Peter H. Dutton; Christine A. Madden (Frontiers in Marine Science, 2026)
Effective conservation and enforcement strategies for marine turtles depend on understanding population structure, connectivity, and the geographic origins of turtles impacted by threats such as bycatch, overexploitation, and illegal trade. However, mitochondrial DNA (mtDNA) data remain fragmented across studies, with inconsistent sequence lengths, haplotype nomenclature, and metadata standards limiting their application in conservation, management, and wildlife forensics. To address these challenges, we developed ShellBank, a global marine turtle genetic traceability toolkit and open-access mtDNA database that consolidates and standardizes more than 20,000 mtDNA control-region sequences from published literature and verified contributed datasets. The platform harmonizes sequence lengths, haplotype nomenclature, and associated metadata, and provides tools to search haplotypes, access population-level baselines, extract frequency tables for Mixed Stock Analysis (MSA), and explore connectivity among nesting, in-water, and trade datasets. We demonstrate its utility through two case studies. First, mtDNA from a tortoiseshell seizure in the United Kingdom was compared against the ShellBank baseline, identifying likely source rookeries in the Eastern Caribbean and highlighting priority sampling gaps. Second, reanalysis of a hawksbill turtle foraging aggregation on the Great Barrier Reef using an expanded reference baseline substantially altered previous stock assignment estimates, corroborated flipper-tag and satellite-tracking data, and confirmed multi-stock connectivity across the western Pacific. By centralizing and standardizing global marine turtle mtDNA data, ShellBank improves the resolution, accuracy, transparency, and application of genetic traceability for conservation, management, and enforcement, strengthening the ability of researchers, managers, decision-makers, and enforcement agencies to identify source regions, detect population-level impacts, understand ecological connectivity, and guide evidence-based conservation actions.

Mycobacterium gordonae (Actinomycetota: Mycobacteriales: Mycobacteriaceae) Infecting Captive‐Reared Laurel Dace, Chrosomus saylori (Cypriniformes: Leuciscidae) in North America - Daniel Gordillo‐González; Steven P. Ksepka; Haley R. Dutton; Kamila Cajiao‐Mora; John H. Brule; Bernard R. Kuhajda; Anna L. George; Stephen A. Bullard (Journal of Fish Diseases, 2026)
A captive‐reared cohort of Laurel Dace, Chrosomus saylori (Skelton 2001) (Cypriniformes: Leuciscidae), a federally‐endangered species endemic to several streams in eastern Tennessee's Cumberland Plateau, exhibited signs of morbidity and trickling mortalities in a recirculating aquaculture system. Ziehl‐Neelsen (ZN) staining revealed acid‐fast rod‐shaped bacteria within necrotic and intracellular lesions affecting the eye, swim bladder, spleen, and ovary. Histopathology showed granulomatous inflammation characterised by macrophages, multinucleated giant cells, and eosinophilic exudates. The eye, swim bladder, and ovary were particularly impacted: the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates; the swim bladder exhibited granulomatous inflammation with extensive fibrosis; the ovary contained caseous granulomas; and the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates. PCR amplification of the hsp65 gene (316 bp) from formalin‐fixed and paraffin‐embedded lesioned tissues was identical (100% similar; 424 bp fragment) to that of the type strain of Mycobacterium gordonae Bojalil et al. 1962 (AF547840). This is the first report of an infection by M. gordonae in Laurel Dace; the first record of this bacterium causing a lesion in the swim bladder, eye, or ovary; and the first record of M. gordonae from a freshwater fish in North America.

Freeze Tolerance of Amyloodinium ocellatum (Myzozoa: Blastodiniales) - Robert D. Gonzales; Haley R. Dutton; Reginald B. Blaylock; Stephen A. Bullard; Eric A. Saillant (Journal of Fish Diseases, 2026)
Amyloodinium ocellatum causes epizootics in marine fish hatcheries. Frozen, wild fish, often used as food in aquaculture, could introduce the disease. We investigated the parasite's ability to survive, reproduce and infect a host after freezing. Infected gills were frozen at −20°C for either 0, 24, 36, 48, or 72 h. Parasite viability was assessed first by placing thawed infected gills into tanks with naïve fish. Gills of the exposed fish were examined on day 0 and on days 4 and 7 post‐exposure. Tomonts from infected gills in all freeze durations produced infections. However, dinospore production decreased and infections took longer to establish in fish exposed to tomonts from the 72 h treatment. Second, eight tomonts from each freeze duration were placed in 5 mL of 25 ppt artificial seawater at 22°C in individual wells of a 12‐well plate and monitored for hatching. Ninety seven percent of tomonts from all treatments hatched. Tomonts frozen for up to 72 h survived, reproduced and infected fish, but dinospore production decreased as freeze duration increased. Extrapolation from the rate of reduction in dinospore production over the freeze durations tested suggests that a freeze duration of 237 h could inactivate all tomonts.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Catadiscus marielaosornae n. sp. (Digenea: Diplodiscidae) infecting the intestine of Peters’ thin-toed frog, Leptodactylus petersii (Steindachner) (Anura: Leptodactylidae) from the Yahuarcaca Lake System, Amazon River (Leticia, Colombia), with phylogenetic analysis - Kamila Cajiao-Mora; José Rancés Caicedo-Portilla; John H. Brule; Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2025)
We describe Catadiscus marielaosornae Cajiao-Mora and Bullard n. sp . (Diplodiscidae) from the intestine of Peters’ thin-toed frog, Leptodactylus petersii (Steindachner) (Anura: Leptodactylidae) from the Yahuarcaca Lake System, Colombia. We assigned our specimens to Catadiscus Cohn, 1904 because they have a smooth-surfaced, pyriform body, centrally-constricted ventro-terminal acetabulum that lacks an accessory sucker, pharynx with extramural sacs, oesophageal bulb, and single testis. The new species differs from all but Catadiscus rodriguezi Caballero, 1955, Catadiscus marinholutzi Freitas and Lent, 1939, and Catadiscus propinquus Freitas and Dobbin, 1956 by having a vitellarium that is confluent anteriorly ( vs . two non-confluent fields). It differs from the aforenamed congeners by having a ventral common genital pore that opens anterodextral to the oesophageal bifurcation, round vitelline follicles that become confluent anterior to the testis, and a 1: 2–3 ratio of acetabulum: testis width. Our 28S phylogenetic analysis recovered the new species sister to C. marinholutzi , and Diplodiscidae as paraphyletic, with Catadiscus sister to a clade comprising a sequence ascribed to Chiorchis fabaceus (Diesing, 1838) Fischoeder, 1901 (Cladorchiidae), and sequences of three species of Diplodiscus Diesing, 1836. The species description herein includes several features pertaining to the acetabulum, female genitalia, and excretory system that could comprise useful character states with which to more readily classify and diagnose diplodiscid species and genera. To our knowledge, this is the first record of a digenean infecting Peters’ thin-toed frog, and it is also the first record of any parasite infecting any ditch frog ( Leptodactylus spp.) from Colombia.

Population structure and genetic diversity of leatherback turtles (Dermochelys coriacea) in Bird’s Head Seascape, Papua-Indonesia - Abdul Hamid A. Toha; Deasy Lontoh; Fitryanti Pakiding; Andhika P. Prasetyo; Lisa M. Komoroske; Peter H. Dutton (Frontiers in Marine Science, 2025)
Leatherback (Dermochelys coriacea) populations are endangered globally and there is a need to better understand their genetic diversity and structure in order to inform conservation efforts. Most nesting in the western Pacific is concentrated in the Bird’s Head Seascape (BHS) region of West Papua, Indonesia. Previous genetic assessment based on limited mtDNA sequences inadequately represented the demographic complexity that is now evident for West Papua leatherbacks. In this study, we quantified the genetic diversity, connectivity and structure for leatherback populations in the BHS by integrating nuclear and mitochondrial (mt) DNA data. We compared 763-bp sequences of the mtDNA control region and data from 17 microsatellite loci at two beaches, Jeen Yessa (JY) and Jeen Syuab (JS) that represent temporally separated nesting populations. We then leveraged reduced-representation (RAD-capture) and whole genome resequencing approaches to generate genome-wide SNPs. We detected low genetic diversity for all datatypes. A total of 11 mtDNA haplotypes were identified, including two new haplotypes and three previously reported from Atlantic populations. Pairwise tests of haplotype and genotype (microsatellite) frequencies found no evidence of structure between the JY (boreal summer) and JS (boreal winter) populations. Furthermore, admixture and principal components analyses of genomic SNP datasets did not identify any clear genetic structure. These results suggest that the BH leatherbacks represent a single genetic stock based on current criteria for defining population Management Units for sea turtles. This study provides the basis for further population structure assessment that includes other nesting sites in Indonesia and the broader western Pacific.

Isolation of a CTX-M-55 (ESBL)-Producing Escherichia coli Strain of the Global ST6448 Clone from a Captive Orangutan in the USA - Carly M. Smith; Melissa Anacker; Durward L. Bevis; Nicole A. M. Dutton; Dan Powell; Richard William McLaughlin (Current Microbiology, 2024)

Landscape diversity promotes stable food‐web architectures in large rivers - Eric A. Scholl; Wyatt F. Cross; Christopher S. Guy; Adeline J. Dutton; James R. Junker (Ecology Letters, 2023)
Uncovering relationships between landscape diversity and species interactions is crucial for predicting how ongoing land‐use change and homogenization will impact the stability and persistence of communities. However, such connections have rarely been quantified in nature. We coupled high‐resolution river sonar imaging with annualized energetic food webs to quantify relationships among habitat diversity, energy flux, and trophic interaction strengths in large‐river food‐web modules that support the endangered Pallid Sturgeon. Our results demonstrate a clear relationship between habitat diversity and species interaction strengths, with more diverse foraging landscapes containing higher production of prey and a greater proportion of weak and potentially stabilizing interactions. Additionally, rare patches of large and relatively stable river sediments intensified these effects and further reduced interaction strengths by increasing prey diversity. Our findings highlight the importance of landscape characteristics in promoting stabilizing food‐web architectures and provide direct relevance for future management of imperilled species in a simplified and rapidly changing world.

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Exploring the Use of SEM–EDS Analysis to Measure the Distribution of Major, Minor, and Trace Elements in Bottlenose Dolphin (Tursiops truncatus) Teeth - Meaghan A. McCormack; Wayne E. McFee; Heidi R. Whitehead; Sarah Piwetz; Jessica Dutton (Biological Trace Element Research, 2022)

Resurrection and emendation of Pseudoparamacroderoides Gupta & Agrawal, 1968 (Digenea: Macroderoididae), description of a new species from Vietnam, and comments on the systematics of macroderoidid genera - Triet N. Truong; Stephen S. Curran; Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2021)

Mitochondrial DNA Profiling to Combat the Illegal Trade in Tortoiseshell Products - Erin L. LaCasella; Michael P. Jensen; Christine A. Madden Hof; Ian P. Bell; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2021)
Hawksbill turtles ( Eretmochelys imbricata ) are exploited for their beautiful shell known as tortoiseshell or bekko, making them extremely vulnerable in the illegal global trade of tortoiseshell products. In this study, we developed an effective, standardized method using a commercially available kit to extract DNA and obtain informative mitochondrial DNA (mtDNA) control region sequences (~800 bp) from hawksbill turtle products in order to trace the sample back to a likely stock origin. We also sequenced additional skin samples from nesting beaches of Milman Island, Australia and Arnavon Island, Solomon Islands to add to the baseline data for hawksbill turtles in the Indo-Pacific. Our results indicate that nine of the 13 tortoiseshell products obtained from Papua New Guinea and Solomon Islands were from turtles with haplotypes found primarily at the Solomon Islands rookery and did not match those from nesting populations in Australia or SE Asia, with the exception of one haplotype also found in 3% of turtles at Milman Island. We also found that 23% of the market samples have haplotypes only documented in foraging populations, which illustrates the urgent need for more extensive sampling of rookeries to fill gaps in the reference baseline database. Nevertheless, our study results demonstrate an effective methodology for obtaining DNA of sufficient quantity and quality from hawksbill turtle products.

Single nucleotide polymorphism markers for genotyping hawksbill turtles (Eretmochelys imbricata) - Shreya M. Banerjee; Lisa M. Komoroske; Amy Frey; Brittany Hancock-Hanser; Phillip A. Morin; Frederick I. Archer; Suzanne Roden; Alexander Gaos; Michael J. Liles; Peter H. Dutton (Conservation Genetics Resources, 2020)

A new species and emendation of the seldom reported Enterohaematotrema Mehra, 1940 (Digenea: Schistosomatoidea), including a revised phylogenetic hypothesis for turtle blood flukes - Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2020)

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.

Genetic analysis and satellite tracking reveal origin of the green turtles in San Diego Bay - Peter H. Dutton; Robin A. LeRoux; Erin L. LaCasella; Jeffrey A. Seminoff; Tomoharu Eguchi; Donna L. Dutton (Marine Biology, 2019)

Long-term trends in the foraging ecology and habitat use of an endangered species: an isotopic perspective - Elizabeth D. Hetherington; Jeffrey A. Seminoff; Peter H. Dutton; Lisa C. Robison; Brian N. Popp; Carolyn M. Kurle (Oecologia, 2018)

Late Holocene inter-annual temperature variability reconstructed from the δ 18 O of archaeological Ostrea angasi shells - S. Tynan; B. Opdyke; A. Dutton; M. Walczak (Australian Journal of Earth Sciences, 2017)

Stable carbon isotopes (δ13C) of total organic carbon and long-chain n-alkanes as proxies for climate and environmental change in a sediment core from Lake Petén-Itzá, Guatemala - Jennifer L. Mays; Mark Brenner; Jason H. Curtis; Kathryn V. Curtis; David A. Hodell; Alex Correa-Metrio; Jaime Escobar; Andrea L. Dutton; Andrew R. Zimmerman; Thomas P. Guilderson (Journal of Paleolimnology, 2017)

Fine-Scale Monitoring of Routine Deep Dives by Gravid Leatherback Turtles during the Internesting Interval Indicate a Capital Breeding Strategy - Junichi Okuyama; Jeffrey A. Seminoff; Peter H. Dutton; Scott R. Benson (Frontiers in Marine Science, 2016)

Weighing the Evidence of Common Beliefs in Obesity Research - Krista Casazza; Andrew Brown; Arne Astrup; Fredrik Bertz; Charles Baum; Michelle Bohan Brown; John Dawson; Nefertiti Durant; Gareth Dutton; David A. Fields; Kevin R. Fontaine; Steven Heymsfield; et al. (Critical Reviews in Food Science and Nutrition, 2015)

Diseases of captive yellow seahorse Hippocampus kuda B leeker, pot‐bellied seahorse Hippocampus abdominalis L esson and weedy seadragon Phyllopteryx taeniolatus ( L acépède) - V LePage; J Young; C J Dutton; G Crawshaw; J A Paré; M Kummrow; D J McLelland; P Huber; K Young; S Russell; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2015)
Seahorses, pipefish and seadragons are fish of the F amily S yngnathidae. From 1998 to 2010, 172 syngnathid cases from the T oronto Z oo were submitted for post‐mortem diagnostics and retrospectively examined. Among the submitted species were yellow seahorses Hippocampus kuda Bleeker ( n = 133), pot‐bellied seahorses Hippocampus abdominalis Lesson ( n = 35) and weedy seadragons Phyllopteryx taeniolatus ( L acépède; n = 4). The three most common causes of morbidity and mortality in this population were bacterial dermatitis, bilaterally symmetrical myopathy and mycobacteriosis, accounting for 24%, 17% and 15% of cases, respectively. Inflammatory processes were the most common diagnoses, present in 117 cases. Seven neoplasms were diagnosed, environmental aetiologies were identified in 46 cases, and two congenital defects were identified.

Enhancing the TurtleWatch product for leatherback sea turtles, a dynamic habitat model for ecosystem‐based management - Evan A. Howell; Aimee Hoover; Scott R. Benson; Helen Bailey; Jeffrey J. Polovina; Jeffrey A. Seminoff; Peter H. Dutton (Fisheries Oceanography, 2015)
Fishery management measures to reduce interactions between fisheries and endangered or threatened species have typically relied on static time‐area closures. While these efforts have reduced interactions, they can be costly and inefficient for managing highly migratory species such as sea turtles. The NOAA TurtleWatch product was created in 2006 as a tool to reduce the rates of interactions of loggerhead sea turtles with shallow‐set longline gear deployed by the Hawaii‐based pelagic longline fishery targeting swordfish. TurtleWatch provides information on loggerhead habitat and can be used by managers and industry to make dynamic management decisions to potentially reduce incidentally capturing turtles during fishing operations. TurtleWatch is expanded here to include information on endangered leatherback turtles to help reduce incidental capture rates in the central North Pacific. Fishery‐dependent data were combined with fishing effort, bycatch and satellite tracking data of leatherbacks to characterize sea surface temperature ( SST ) relationships that identify habitat or interaction ‘hotspots’. Analysis of SST identified two zones, centered at 17.2° and 22.9°C, occupied by leatherbacks on fishing grounds of the Hawaii‐based swordfish fishery. This new information was used to expand the TurtleWatch product to provide managers and industry near real‐time habitat information for both loggerheads and leatherbacks. The updated TurtleWatch product provides a tool for dynamic management of the Hawaii‐based shallow‐set fishery to aid in the bycatch reduction of both species. Updating the management strategy to dynamically adapt to shifts in multi‐species habitat use through time is a step towards an ecosystem‐based approach to fisheries management in pelagic ecosystems.

Calibration and combination of dynamical seasonal forecasts to enhance the value of predicted probabilities for managing risk - John A. Dutton; Richard P. James; Jeremy D. Ross (Climate Dynamics, 2013)

Sources of groundwater pumpage in a layered aquifer system in the Upper Gulf Coastal Plain, USA - Yun Huang; Bridget R. Scanlon; Jean-Philippe Nicot; Robert C. Reedy; Alan R. Dutton; Van A. Kelley; Neil E. Deeds (Hydrogeology Journal, 2012)

Abundance and survival rates of green turtles in an urban environment: coexistence of humans and an endangered species - Tomoharu Eguchi; Jeffrey A. Seminoff; Robin A. LeRoux; Peter H. Dutton; Donna L. Dutton (Marine Biology, 2010)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

Simultaneous occurrence of mycotoxins in human food commodities from Cameroon - Patrick B. Njobeh; Mike F. Dutton; Susan H. Koch; Anil A. Chuturgoon; Stoycho D. Stoev; Joseph S. Mosonik (Mycotoxin Research, 2010)

Complex etiology and pathology of mycotoxic nephropathy in South African pigs - Stoycho D. Stoev; Stefan Denev; Mike F. Dutton; Patrick B. Njobeh; Joseph S. Mosonik; Paul A. Steenkamp; Iordan Petkov (Mycotoxin Research, 2010)

Tetranucleotide markers from the loggerhead sea turtle (Caretta caretta) and their cross-amplification in other marine turtle species - Brian M. Shamblin; Brant C. Faircloth; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Peter H. Dutton; Amy Frey; Campbell J. Nairn (Conservation Genetics, 2009)

Intra-community spatial variation of size-fractionated organic compounds in Long Beach, California - Margaret A. Krudysz; Steven J. Dutton; Gregory L. Brinkman; Michael P. Hannigan; Philip M. Fine; Constantinos Sioutas; John R. Froines (Air Quality, Atmosphere & Health, 2009)

Leatherback turtles as oceanographic indicators: stable isotope analyses reveal a trophic dichotomy between ocean basins - Bryan P. Wallace; Jeffrey A. Seminoff; Susan S. Kilham; James R. Spotila; Peter H. Dutton (Marine Biology, 2006)

Biological Activity of Cry1Ab Toxin Expressed by Bt Maize Following Ingestion by Herbivorous Arthropods and Exposure of the Predator Chrysoperla carnea - L. B. Obrist; A. Dutton; J. Romeis; F. Bigler (BioControl, 2006)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Origins of green turtle ( Chelonia mydas ) feeding aggregations around Barbados, West Indies - K. Luke; J. A. Horrocks; R. A. LeRoux; P. H. Dutton (Marine Biology, 2004)

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Cytotoxicity of aflatoxin B1 and its chemically synthesised epoxide derivative on the A549 human epithelioid lung cell line - Thesla Palanee; Michael F. Dutton; Anil A. Chuturgoon (Mycopathologia, 2001)

Biological control of Chenopodium album L. in Europe - J. Netland; L.C. Dutton; M.P. Greaves; M. Baldwin; M. Vurro; A. Evidente; G. Einhorn; P.C. Scheepens; L.W. French (BioControl, 2001)

Personality in Captive Chimpanzees: Use of a Novel Rating Procedure - Diane M. Dutton; Roger A. Clark; David W. Dickins (International Journal of Primatology, 1997)

Flight activity assessment of the egg parasitoidTrichogramma brassicae (Hym.: Trichogrammatidae) in laboratory and field conditions - A. Dutton; F. Bigler (BioControl, 1995)